CORYNEBACTERIUM TRIAD IN SOLDIERS - Brzeziński Piotr (Our Dermatology Online, 2010)
Background: Corynebacterial infection is a common condition in soldiers. Pitted keratolysis (PK), a bacterial infection confined to the plantar stratum corneum, does not severely impede patient activity but can be unpleasant and embarrassing because of its ''rotten'' odor. The incidence of PK in soldiers has been reported to be between 1,5% and 77.1%. Erythrasma is a superficial infection caused by Corynebacterium minutissimum and affects the major skin folds and the interdigital regions of the feet. It is characterized by erythematous, brown, scaly patches and maceration, and exhibits coral-red fluorescence under Wood light. Trichomycosis axillaris (TMA) is caused by the Corynebacterium tenuis. Patients affected by trichomycosis axillaris present with complaints of a disagreeable underarm odor and a history of hyperhidrosis and poor hygiene. Examination reveals the underarm hair to be coated with black, yellow-white or reddish deposits.Objective: The aim of this study was to determine the frequency corynebacterium triad in soldiers (pitted keratolysis, erythrasma, trichomycosis axillaris)Methods: The study involved 1694 men, soldiers in age about 23 years, (in period 5 months (-8-12.2008)). 103 persons, whose dermatologic symptoms/changes were analysed, were qualified for the research. Reconnaissance put on base of characteristic clinical sign and under Wood light.Results: Incidence of PK observed at 103 patients (which make up 6,08% of 1694 soldiers). EA diagnosed at 15 soldiers (14,56% of 103 patients), and TMA was diagnosed of 3 patients (2,91% of 103 patients). The coexistence are summarized as follows: erythrasma and PK; 15 of 103 patients (14,56%), TMA and PK in 3 of 103 patients (2,91%). The coexistence of rythrasma, TMA, and PK was noted in 1 patients (0,97%).Conclusions: Corynebacterial infection is a common condition in soldiers. In most cases/most often development of PK is observed. Our results demonstrate that either erythrasma or TMA can be associated with PK. We suggest that a closer, wider inspection is required to rule out the coexistence of the other. corynebacterial infections (Erythrasma, TMN) when a dermatologist encounters PK.